1993
DOI: 10.1007/bf01877421
|View full text |Cite
|
Sign up to set email alerts
|

Histological analysis of IL-2 induced regression of murine solid SL2-tumors

Abstract: When DBA/2 mice are inoculated both intraperitoneally (i.p.) and subcutaneously (s.c.) with syngeneic SL2 lymphoma cells and treated i.p. on day 10-14 with 20,000 units IL-2/day, about 50% of the mice reject both the ascitic tumour and the s.c. tumour. During IL-2 therapy large areas of necrosis appear in the solid SL2 tumours between day 12 and 15. Immunohistochemical studies show that only a small number of infiltrating cells is present in the tumours. The percentage of macrophages (MHC-II+) in the tumours i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…IL-2 has been shown to inhibit (12,13) or induce (14,15) vascularity in different systems. IL-2 has also been reported to cause necrosis or induce an antitumor response that may involve lymphocytes (16,17), neutrophils, macrophages (18,19), NK cells (20,21), and/or T cells (22,23).…”
Section: Intratumoral Il-2 Therapy Mediates Local Destruction Of Tumomentioning
confidence: 99%
See 2 more Smart Citations
“…IL-2 has been shown to inhibit (12,13) or induce (14,15) vascularity in different systems. IL-2 has also been reported to cause necrosis or induce an antitumor response that may involve lymphocytes (16,17), neutrophils, macrophages (18,19), NK cells (20,21), and/or T cells (22,23).…”
Section: Intratumoral Il-2 Therapy Mediates Local Destruction Of Tumomentioning
confidence: 99%
“…We observed increased necrosis in some of our IL-2-treated mice (data not shown). A few studies have shown that IL-2 can affect blood vessels by increasing (14,15) or decreasing vasculature (12,13). Similarly, IL-2 has been shown to trigger the vascular leakage system, which results in endothelial cell damage (45).…”
Section: Multiple Mechanisms Are Responsible For the Antitumor Responmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, IL-2 treatment might disturb the tumor vascular supply. In this context Maas et al [18] showed, in a syngeneic mouse model, that IL-2-mediated tumor regression was dependent on T helper cells but also associated with stagnation of intratumoral blood¯ow. Furthermore, they showed that intratumorally injected IL-2 did not result in an increased tumor in®ltration by immune cells: only very few immune cells were found to be in contact with tumor cells both in IL-2-treated animals and in control animals.…”
Section: Discussionmentioning
confidence: 99%